2020
DOI: 10.2196/18519
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Steps Toward Mobile Early Intervention for Mothers and Their Infants Exiting the Neonatal Intensive Care Unit: Descriptive Examination

Abstract: Background Neonatal intensive care unit (NICU) history, combined with systemic inequities for mothers of nondominant cultures and mothers who are socioeconomically disadvantaged, places infants at an extraordinary risk for poor developmental outcomes throughout life. Although receipt of early intervention (EI) is the best single predictor of developmental outcomes among children with and at risk for early developmental delays, mothers and infants with the greatest needs are least likely to receive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The neonatal hospitalisation may represent a key window of opportunity for addressing social disparities by reducing financial barriers affecting parental presence, 62 promoting breastfeeding, 62 and facilitating access to follow-up and early intervention programmes. 63 Study designs that integrate information on the families' social circumstances would ensure that research on the effectiveness of interventions targets health and developmental disparities.…”
Section: Discussionmentioning
confidence: 99%
“…The neonatal hospitalisation may represent a key window of opportunity for addressing social disparities by reducing financial barriers affecting parental presence, 62 promoting breastfeeding, 62 and facilitating access to follow-up and early intervention programmes. 63 Study designs that integrate information on the families' social circumstances would ensure that research on the effectiveness of interventions targets health and developmental disparities.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to accessing community-based services, the providers in our study identified completion of referral to early intervention as an important element of information provision for parents which was consistent with previous findings [ 19 ]. In their investigation of possible internet-based interventions for ensuring prompt connection to early intervention (EI) services, Baggett et al found that the “most common reason for mothers and their infants to fall off the path toward intervention was that they could not be contacted after leaving the NICU” [ 20 ]. Parent and provider preferences from our study suggest that, by providing information and referral updates for EI services through a mobile app, the concern for missed referrals in this vulnerable patient population could be improved upon.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, historical experiences of harm within medical and mental health systems have yielded high levels of distrust ( 19 ). Consequently, extreme inequities have resulted in minoritized populations, who are most in need of support being least likely to access and engage in them ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%